Second formant transition duration in fluent speech of person who stutter - Hamidreza Tadayon; Bijan Shafiei; Akbar Hasanzade (Vesnu Publications, 2015)
Abstract Introduction: results of researches on acoustic and motor aspects of speech of persons who stutter have shown that the perceptually fluent speech of stutterers differs from the speech of nonstutterers. One of these encoding and processing  aspects of speech that measured in different studies is vowel formant transition features. Because variations in formant structure along the temporal and frequency domains reflect articulatory dynamics especially of the tongue, in study of motor speech ability of persons who stutter, this feature can be used. The purpose of this study is to compare the formant transition duration in fluent speech of those who stutter and those who do not. Materials and methods: In this descriptive-analytic study, 20 PWS and 20 normal counterparts, were asked to read 9 speech samples that insert in a carrier phrase. The responses were recorded and  the duration were measured in milisecond by Praat software. Results: The results of the study showed that the average of formant transiotion duration in PWS was lower than that of normal subjects  however this difference did not reach statistical significance. Conclusion: according to the result of this study motor speech processing  in PWS is different with normal subject and the speed of articulator movement in PWS is faster than PWNS. Key words: stuttering, second formant transition, Praat software